Mechanical and durability properties of fly ash geopolymer concrete containing recycled coarse aggregates - Shaikh, Faiz (Elsevier BV, 2016)
© 2016This paper presents mechanical and durability properties of geopolymer concrete containing recycled coarse aggregate (RCA). The RCA is sourced from local construction and demolition (C&D) waste in Perth, Australia. The RCA is used as a partial replacement of natural coarse aggregate (NCA) in geopolymer concrete at 15%, 30% and 50% by wt. which corresponds to series two, three and four, respectively, while the geopolymer concrete containing 100% NCA is control and is considered as the first series. Class F fly ash is used as the source material for the geopolymer and 8 M sodium hydroxide and sodium silicate alkali activators are used to synthesise the fly ash geopolymer in this study. In all four series a constant alkali activator to fly ash ratio is used. Compressive strength, indirect tensile strength and elastic modulus of above geopolymer concrete are measured at 7 and 28 days, while sorptivity, immersed water absorption and volume of permeable voids of above geopolymer concrete are measured at 28 days. Relevant Australian standards are used to measure all the above properties except the sorptivity which is measured according to ASTM standard. Results show that the compressive strength, indirect tensile strength and elastic modulus of geopolymer concrete decrease with an increase in RCA contents, which is also true for both 7 and 28 days. Excellent correlations of compressive strength with indirect tensile strength and elastic modulus are also observed in geopolymer concrete containing RCA. Existing empirical models for cement concrete and geopolymer concrete containing NCA underestimate and overestimate the indirect tensile strength and elastic modulus, respectively of geopolymer concrete containing RCA. The measured durability properties such as sorptivity, water absorption and volume of permeable voids of geopolymer concrete were also adversely affected by the incorporation of RCA and these properties increase with an increase in RCA contents. The effects of RCA on the measured mechanical and durability properties of geopolymer concrete follow similar trend in cement concrete. Very good correlations of compressive strength with volume of permeable voids and water absorption of geopolymer concrete containing RCA are also observed, while the correlation between the compressive strength and the sorptivity is not that strong.